Images Of Self-Treatment In Patients Of Hallucinations - Aap Apipudin; Irpan Ali Rahman; Dede Sumiati; Dini Nurfauziyah; Fanny Khalifa Latifah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Purpose: this study was to describe the knowledge of self-care in patients with hallucinatory mental disorders such as bathing, dressing and decorating, eating and drinking, defecating and urinating, nail clippers, and toothbrushes. Methods: this research is a quantitative descriptive method using a cross sectional design. The sample in this study were 20 respondents with hallucinatory mental disorders at the Mentari Hati Tasikmalaya Foundation. Results: description of self-care knowledge in hallucinatory patients with 20 respondents. In the female sex, as many as 15 people got an average self-care knowledge of 34%, while in men there were 5 people with an average more than women, namely 35. For the average self-care knowledge of men and female is 34.5. Conclusion: this study shows that self-care knowledge in hallucinatory mental disorder patients is lacking.